A multifunctional benzothiadiazole-based fluorescence sensor for Al3+, Cr3+ and Fe3 - Shu-Li, Yao; Yu-Chen, Xiong; Xue-Mei Tian; Sui-Jun, Liu; Xu, Hui; Teng-Fei, Zheng; Jing-Lin, Chen; He-Rui, Wen (CrystEngComm, 2021)
A new benzothiadiazole-based MOF {[Zn(BIBT)(oba)]·DMA}n (JXUST-3, BIBT = 4,7-bi(1H-imidazol-1-yl)benzo-[2,1,3]thiadiazole and H2oba = 4,4′-oxybisbenzoate) has been solvothermally synthesized and characterized by single crystal X-ray diffraction, IR spectroscopy and TGA. The fluorescence studies suggest that JXUST-3 could simultaneously selectively sense trivalent metal ions including Al3+, Cr3+ and Fe3+ by a turn-off effect, and the detection limits are 0.055, 0.049 and 0.056 μM, respectively. Moreover, JXUST-3 exhibits relatively good thermal and chemical stabilities and reusability. The fluorescent test paper also displayed an obvious turn-off effect, indicating that JXUST-3 can be used as a potential multi-response fluorescent probe. The possible quenching mechanisms of JXUST-3 for Al3+ and Fe3+ were competitive energy absorption, and for Cr3+ ions, they were competitive energy absorption and weak interactions between Cr3+ and the framework. Therefore, JXUST-3 could be viewed as a transition metal MOF fluorescence sensor for Al3+, Cr3+ and Fe3+ by the turn-off effect, simultaneously.